Lacanian Psychotherapy : Theory and Practical Applications. - Miller, Michael J. (Taylor & Francis, 2011)
The work of Jacques Lacan is associated more with literature and philosophy than mainstream American psychology, due in large part to the dense language he employs in articulating his theory - often at the expense of clinical illustration. As a result, his contributions are frequently fascinating, yet their utility in the therapeutic setting can be difficult to pinpoint. Lacanian Psychotherapy€fills in this clinical gap by presenting theoretical discussions in clear, accessible language and applying them to several chapter-length case studies, thereby demonstrating their clinical relevanc.